2011
DOI: 10.1111/j.1465-3435.2011.01493.x
|View full text |Cite
|
Sign up to set email alerts
|

Student Teachers' Perceptions of the Effectiveness of their Initial Preparation

Abstract: What influences how well‐prepared student teachers feel towards working in schools upon completion of their initial teacher preparation (ITP)? In order to investigate this question, we used a path analysis using data from a longitudinal study investigating the experiences of trainee and early career phase teachers in England. The data were generated via self‐complete questionnaires and follow‐up telephone interviews with 1,322 trainees. Those on undergraduate or school‐based programmes felt better prepared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…As is true in this case, the vast majority of teacher education studies often had limited access to teacher preparation programs and showed data from individual teacher preparation schools. Giannakaki, Hobson & Malderez (2011) analysis of data from the "Becoming a Teacher" study, a large-scale longitudinal (2003)(2004)(2005)(2006)(2007)(2008)(2009)) study of trainee and early career teachers in England, serves as one of few examples of scholarly works that went beyond single teacher preparation programs.…”
Section: Introductionmentioning
confidence: 99%
“…As is true in this case, the vast majority of teacher education studies often had limited access to teacher preparation programs and showed data from individual teacher preparation schools. Giannakaki, Hobson & Malderez (2011) analysis of data from the "Becoming a Teacher" study, a large-scale longitudinal (2003)(2004)(2005)(2006)(2007)(2008)(2009)) study of trainee and early career teachers in England, serves as one of few examples of scholarly works that went beyond single teacher preparation programs.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the majority of trainee teachers in England follow a postgraduate, thirty-six-week programme to achieve qualification and status, the few studies of their experiences (Smith, 2005; Giannakaki et al. , 2011; Hobson et al.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Given that the majority of trainee teachers in England follow a postgraduate, thirty-sixweek programme to achieve qualification and status, the few studies of their experiences (Smith, 2005;Giannakaki et al, 2011;Hobson et al, 2006) indicate that there are two main areas of priority: acquiring the required level and range of subject knowledge and translating it to practice (pedagogical content knowledge); and building professional attributes.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Although overcoming fragmentation in a teacher-training program can be difficult (Giannakaki, Hobson & Malderez, 2011) 8. Teachers establish relationships with students that respect human dignity.…”
Section: Program Coherencementioning
confidence: 99%